Fuzzy neural network-based system identification of multi-storey shear buildings. Issue 3 (March 2017) - Chakraverty, S.; Sahoo, Deepti
Abstract This paper uses fuzzy neural network modelling for the identification of structural parameters of multi-storey shear buildings. First the identification has been done using response of the structure subject to ambient vibration with fuzzy initial condition. Then forced vibration with horizontal displacement in fuzzified form has been used to investigate the identification procedure. The model has been developed to handle the data in fuzzified form for multi-storey shear structure, and the procedure is tested for the identification of the stiffness parameters of simple example problems using the prior values of the design parameters.